2013
DOI: 10.1111/cid.12051
|View full text |Cite
|
Sign up to set email alerts
|

Nonremoval of Immediate Abutments in Cases Involving Subcrestally Placed Postextractive Tapered Single Implants: A Randomized Controlled Clinical Study

Abstract: The nonremoval of abutments placed at the time of the surgery improves the stability of healed soft and hard tissues around the immediately restored, subcrestally placed tapered single maxillary implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 19 publications
(37 reference statements)
6
78
0
13
Order By: Relevance
“…; Degidi et al. ; Grandi et al. ), also with similar outcomes to the results of the present clinical trial.…”
Section: Discussionsupporting
confidence: 89%
“…; Degidi et al. ; Grandi et al. ), also with similar outcomes to the results of the present clinical trial.…”
Section: Discussionsupporting
confidence: 89%
“…The published studies evaluating peri‐implant marginal bone loss concerning abutment disconnections showed considerable variety in methodology and results. Three randomized clinical trials involved implants positioned in fresh extraction sockets (Canullo et al, ; Degidi et al, ; Grandi et al, ) and two of them observed less bone resorption for implants with no abutment disconnection (Canullo et al, ; Grandi et al, ). In another study that used fresh extraction sockets and healed sites (Bressan et al, ; Esposito et al, ; Luongo et al, ), no differences were observed at 4‐month follow‐up (Luongo et al, ), however, repeated abutment disconnections increased bone loss after one and 3 years (Bressan et al, ; Esposito et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the implants were restored with cement‐retained prostheses, which may undergo interference from other factors such as the presence of luting agent excess in the peri‐implant space (Linkevicius, Puisys, Vindasiute, Linkeviciene, & Apse, ; Linkevicius, Vindasiute, et al, ). Another relevant aspect that could interfere with the results was the inclusion of smoking volunteers in all these previous studies (Bressan et al, ; Canullo et al, ; Degidi et al, ; Esposito et al, ; Grandi et al, , ; Koutouzis et al, ; Luongo et al, ; Molina et al, ). To avoid this type of influence (Gothberg, Grondahl, Omar, Thomsen, & Slotte, ), only non‐smokers were included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlacionando os resultados encontrados nesta pesquisa com a revisão de literatura prévia, destacam-se trabalhos onde a instalação única do pilar protético, permanente e definitiva, no momento da instalação do implante, proporciona um efeito positivo sobre a retenção e a estabilidade do tecido ósseo marginal (DEGIDI et al, 2013c;KOUTOUZIS et al, 2011). Adicionalmente, Castro et al (2014) Na comparação dessas respostas com as dos outros animais, é possível inferir que o animal 2 apresenta uma boa característica biológica cicatricial em relação ao tecidos ósseos, conjuntivos e epiteliais bucais, sendo esta característica possivelmente superior à presente nos outros animais.…”
Section: Análise Histológica Descritiva Dos Grupos Controle E Experimunclassified